Long-Term Buyer-Supplier Relationship Analysis - Aristya, Tania; Utami, Christina Whidya; Sumaji, Yoseva Maria (International Business Management - Universitas Ciputra, 2025)
This study discusses the factors contributing to the long-term relationship between a business and its suppliers. The problem faced by the company is the unfulfilled realization of the fulfillment of the copra raw material. The competition among copra business players and the potential suppliers choosing to sell to competitors causes this problem. This research aims to determine the factors contributing to the sustainability of the relationship between the company and its suppliers. The method used in this study is a quantitative method with an exploratory factor analysis approach using the SPSS analysis tool. The population in this study consists of 45 company suppliers scattered in North Maluku and East Nusa Tenggara. The sampling technique used is saturated sampling, involving all 45 respondents in the population. The data collection method in this research uses a questionnaire with a Likert scale. The results of the factor analysis revealed the formation of five new factors, which are simplifications of the fifteen research variables. These factors are interpersonal Relationships, satisfactory performance, trusted practices, loyalty, and communication synchronization.